Developing The Firm Mosque Model As A Public Health Institution Through The Implementation Of Psychoacoustic On Loudspeaker Systems - Nurida Finahari; Alfiana (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
Voices originating from the mosque, whether they are recitation, incidental activities or daily routine prayers, are still often interpreted as a source of noise. Not only because of the improper arrangement of the loudspeakers, but also because the mosque's recitals or takmirs generally do not understand the psychoacoustic aspect. Psychoacoustic is the study of the effect of sound exposure on the psychological aspects of the listeners. The use of psychoacoustic science could potentially change mosque sounds into therapeutic voices. The voices of recitation-based therapists have been encountered and researched, although in a limited scope. Building a mosque sound management and control system that is consistent within a psychoacoustic framework can transform potential noise into a natural sound that builds public health that runs automatically. The achievement of this hypothesis can be done from the application of a research and / or community service activity by educational institutions or related agencies.